2024
DOI: 10.1111/bph.16408
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast improves disease outcome in SOD1G93A female mice by counteracting oligodendrocyte dysfunction and aberrant glial reactivity

Stefano Raffaele,
Nhung Nguyen,
Marco Milanese
et al.

Abstract: Background and PurposeAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by progressive motor neuron (MN) loss and consequent muscle atrophy, for which no effective therapies are available. Recent findings reveal that disease progression is fuelled by early aberrant neuroinflammation and the loss of oligodendrocytes with neuroprotective and remyelinating properties. On this basis, pharmacological interventions capable of restoring a pro‐regenerative local milieu and re‐esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 117 publications
0
0
0
Order By: Relevance
“…Montelukast is a CysLT1R and GPR17 antagonist, approved as adjuvant therapy for asthma in both children and adults. Montelukast’s neuroprotective and anti-inflammatory effects have been proven in different models of neurodegenerative diseases, including SCI, MS, stroke, amyotrophic lateral sclerosis and Huntington’s [ 139 , 140 , 141 , 142 , 143 , 144 ]. Montelukast’s beneficial effects are likely mediated by its multiple actions on microglia/astrocytes and oligodendrocytes, expressing CyLT1R and GPR17, respectively.…”
Section: Therapeutic Approaches and Targets For Promoting Remyelinati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Montelukast is a CysLT1R and GPR17 antagonist, approved as adjuvant therapy for asthma in both children and adults. Montelukast’s neuroprotective and anti-inflammatory effects have been proven in different models of neurodegenerative diseases, including SCI, MS, stroke, amyotrophic lateral sclerosis and Huntington’s [ 139 , 140 , 141 , 142 , 143 , 144 ]. Montelukast’s beneficial effects are likely mediated by its multiple actions on microglia/astrocytes and oligodendrocytes, expressing CyLT1R and GPR17, respectively.…”
Section: Therapeutic Approaches and Targets For Promoting Remyelinati...mentioning
confidence: 99%
“…Other studies suggested that clemastine modulates the behaviour of other glial cells. In a mouse model of depression, clemastine significantly suppressed microglial M1-like activation and improved hippocampal astrocytic loss [ 144 ]. Of note, a recent paper also demonstrated that clemastine reduces the density of CD11c + microglial cells, a transient population involved in developmental myelination, suggesting that clemastine’s final outcome on myelination may depend on microglia–oligodendrocytes crosstalk [ 150 ].…”
Section: Therapeutic Approaches and Targets For Promoting Remyelinati...mentioning
confidence: 99%